Upaya Peningkatan Keterampilan Bermain Drama Dengan Menggunakan Teknik Oscar Brocket Pada Peserta Didik Kelas XI 4 SMA Negeri 6 Palembang - Ersya, Putri; Lestari, Hikmah (Yayasan Daarul Huda Kruengmane, 2024)
This research is classroom action research (PTK). The research subjects were students of class XI 4 SMA Negeri 6 Palembang, totaling 37 students. This research aims to improve the drama playing skills of class XI 4 students at SMA Negeri 6 Palembang using the Oscar Brocket technique. This research also seeks to integrate Oscar Brocket's techniques into their curriculum, expanding the learning approaches they use. The method used in this research is qualitative descriptive analysis supported by quantitative data to describe the ability to play drama before and after the action. Qualitative analysis was used to record field observations and interview results, while quantitative data was obtained from evaluating drama plays before and after the action was carried out. The data sources used in this research are primary data sources and secondary data sources. This research consists of two cycles. Each cycle consists of four stages, namely planning, implementation or action, observation, and reflection. Data collection techniques used were questionnaires, interviews, observations and documentation of learning activities. Analysis was carried out using qualitative descriptive techniques supported by quantitative data. The validity of the data obtained through validity (process, results and democratic). The results of this research show that the Oscar Brocket technique can improve drama playing skills in class XI 4 students at SMA Negeri 6 Palembang. Students are trained to concentrate with fun techniques. Students will not get bored using this technique because students are invited to imagine everything they can bring. Students are also trained to act according to the characters they play in the script that has been created.